Quality management implementation in higher education : practices, models, and case studies - Sony, Michael, 1981-; Karingada, Kochu Therisa, 1983-; Baporikar, Neeta (IGI Global, 2020)
"This book examines the implementation of quality management systems in research, teaching, learning, administrative processes, and other facets of higher education"- Resumé vydavatel
Keywords: total quality management; vysoké školy; vysokoškolské studium; universities and colleges; college study; elektronické knihy; případové studie; electronic books; case studies